Identification of cervical self-collection as a cervical cancer screening tool (Research, Society and Development, 2022)
Cervical cancer is caused solely by the persistent infection of the Human Papillomavirus (HPV) considered the etiological agent of the disease and transmitted through unprotected sexual intercourse. Cervical self-collection is an alternative to increase the coverage of screening programs in several countries. Some articles were verified that demonstrate the acceptability of this self-collection device, showing the ability to overcome barriers that prevent efficient cervical screening. Currently, studies have been identified around the world that demonstrate the need to implement alternative technologies that facilitate cervical collection and that increase the detection capacity by molecular pathways to minimize the intervention time to minimize the evolution of HPV infection and evolution. for cervical cancer.